MAKNA GELAR HAJI BAGI MASYARAKAT DESA SIPAENRE KECAMATAN KINDANG KABUPATEN BULUKUMBA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
This journal aims to describe the importance of the Hajj title for the people of Sipaenre Village, Kindang District, Bulukumba Regency, and how the impact of the Hajj title on people's lives in Sipaenre Village, Kindang District, Bulukumba Regency. In the explanation of this journal, the type of research used is qualitative research using a symbolic approach method with Sociological theory. Sources of data in this study are primary data sources and secondary data. Then the data collection methods used were observation, interviews, and documentation. The results of research on the importance of the Hajj title for the people of Sipaenre Village, Kindang District, Bulukumba Regency show that the community has several differences in interpreting the Hajj title as well as the Hajj symbols it has. On the one hand, some people think that the Hajj title is something important and mandatory. to mention it because according to him it will lead to sin if it is not mentioned, on the other hand, there are also people who are mediocre in responding to the title of Hajj and the symbols of Hajj who think that it is just a tradition or culture that has been passed down in society and as for the impact Hajj titles in the people of Sipaenre Village, which often makes people who have not made the pilgrimage feel awkward to those who have made the pilgrimage because they feel that people who already have the title of Hajj are people who have more position and privileges.